Comparison of the Nutritional Quality of Branded and Private-Label Food Products Sold in Italy: Focus on the Cereal-Based Products Collected From the Food Labeling of Italian Products Study - Angelino, Donato; Del Bo', Cristian; Pellegrini, Nicoletta; Martini, Daniela; , SINU Young Working Group (Frontiers in Nutrition, 2021)
The packaged foods sold in food stores may be “private-label” products (PL), when branded by the supermarket, and “branded” products (BR). PL products are generally cheaper than the BR counterparts and, from one side, the low price of PL can represent a pivotal driver of purchase. Nevertheless, on the other side, this can be perceived as a sign of general low quality by consumers, when items are compared to their branded counterparts. Thus, the aim of the present study was to compare the nutrient content of BR and PL cereal-based foods currently sold in Italy, by evaluating the nutritional declaration reported on the food pack. A total of 3,775 items were included in the final analysis, with ~58% BR and ~42% PL products, respectively. BR and PL products only differed for the content of some nutrients, such as total fats, saturates, total carbohydrates, proteins and salt for some categories and types. No differences were instead found for energy and sugar contents among any of the categories under study. However, we did not find any consistency in the direction of results. These results could be useful for future education activities aimed to help consumers on making informed food choices.